A Normotensive Patient with Primary Aldosteronism - Xiao Lin; Xiaoyu Miao; Pengli Zhu; Fan Lin (Case Reports in Endocrinology)
This study was to report a case of normotensive patient with primary aldosteronism who was admitted to our department recently. The patient was a 33-year-old male with right adrenal incidentaloma, but without any symptom. He has no history of hypertension, and blood pressure was normal when measured at multiple time points during hospitalization stay. The 24-hour ambulatory blood pressure prompted a normal blood pressure with the existence of circadian rhythm. The patient was diagnosed with primary aldosteronism by screening and confirmatory test. Due to the absence of symptom, surgery was not preferred. Blood pressure was found to be normal with the 2-month follow-up from discharge until now.